Rak materničnega vratu - Jančar, Nina (Medicinski razgledi, 2010)
Cervical cancer is the second most common cancer in women worldwide. It evolves through several stages of precancerous lesions and can therefore be prevented by means of organized screening program. If discovered in an early stage it can also be effectively treated. In Slovenia, the incidence of cervical cancer in the year 2002 has been relatively high compared to average European incidence. Since the introduction of organized national screening program in the year 2003, the number of newly diagnosed cervical cancer cases has already fallen substantially by the year 2008. Squamous celI carcinoma is the most common histological type of cervical cancer, followed by adenocarcinoma and adenosquamous carcinoma.Treatment of cervical carcinoma in early stages is primarily surgical, while radiation and chemo therapy are applied in advanced stages.
Keywords: Adenokarcinom; Cervix Neoplasms; Diagnosis; Papilomavirus človeški; Pathology; Karcinom ploščatocelični; Novotvorba, stadij; Therapy; Papillomavirus, Human; Maternični vrat, novotvorbe; Medicinsko presejanje; Classification; Carcinoma, Squamous Cell; ginekologija; Adenocarcinoma; maternični vrat; Neoplasm Staging; rak (medicina); papiloma virusi; Mass Screening; histologija; diagnostika; zdravljenje